The Ostrich Communal Nesting System. - Bertram, Brian C. R. (Monographs in behavior and ecology., 2014)
As the study of cooperative breeding systems expands, a number of key species form the examples that underpin our general understanding. The ostrich is increasingly becoming such a textbook species, on the basis of the results obtained in Brian Bertram's study of vigilance and egg discrimination in this extraordinary bird. Here Bertram presents new data on the ostrich communal nesting system, in which several females lay in one female's nest, with only one female and the male doing all the work. The Ostrich Communal Nesting System unravels the basis of the cooperation observed, and explains.